2005
DOI: 10.1128/jcm.43.4.1674-1677.2005
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Pooled Urine Specimens for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae in Men Attending Public Sexually Transmitted Infection Clinics in Mumbai, India, by PCR

Abstract: Pooling urogenital specimens for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae by nucleic acid amplification tests is an attractive alternative to individual testing. As pooling can reduce the costs of testing as well as labor, it has been advocated for use in resource-poor settings. However, it has neither been widely adopted nor evaluated for use in developing countries. We evaluated the practical use of pooling first-catch urine (FCU) specimens for the detection of C. trachomatis and N. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 23 publications
0
36
0
1
Order By: Relevance
“…For example, an abnormal urethral discharge and burning or painful micturition (dysuria) in men are considered suggestive of gonorrhoea and chlamydia (Adler 1998), and syndromic guidelines are used to manage symptomatic men in India (Hawkes & Santhya 2002). However, recent studies of Indian men have reported low prevalences of gonorrhoea and chlamydia (Joyee et al 2004;Lindan et al 2005), in conjunction with a high burden of reported symptoms (International Institute for Population Sciences 2001). This suggests that the syndromic guidelines for the treatment of STIs may have low specificity and costeffectiveness among symptomatic Indian men in comparison with other developing countries where the prevalence of STIs is higher (Gilson et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an abnormal urethral discharge and burning or painful micturition (dysuria) in men are considered suggestive of gonorrhoea and chlamydia (Adler 1998), and syndromic guidelines are used to manage symptomatic men in India (Hawkes & Santhya 2002). However, recent studies of Indian men have reported low prevalences of gonorrhoea and chlamydia (Joyee et al 2004;Lindan et al 2005), in conjunction with a high burden of reported symptoms (International Institute for Population Sciences 2001). This suggests that the syndromic guidelines for the treatment of STIs may have low specificity and costeffectiveness among symptomatic Indian men in comparison with other developing countries where the prevalence of STIs is higher (Gilson et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One approach that can reduce costs is to pool (put together) specimens from several patients and test them using a single test (6,7). If a pool tests positive, then each specimen is tested individually to detect the positive sample(s), whereas if the pooled specimens test negative, all individuals are considered infection free (6,7).…”
mentioning
confidence: 99%
“…One approach that can reduce costs is to pool (put together) specimens from several patients and test them using a single test (6,7). If a pool tests positive, then each specimen is tested individually to detect the positive sample(s), whereas if the pooled specimens test negative, all individuals are considered infection free (6,7). A pooling strategy appears to be cost-effective and accurate when NAATs are used to screen blood for HIV (8) and blood-borne hepatitis viruses (9), detect Chlamydia trachomatis and Neisseria gonorrhoeae in urine specimens (7), and identify influenza virus in nasopharyngeal swab samples (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This idea was suggested by Dorfman in 1943 (6) and has been used for the serological diagnosis of infectious diseases. Pooling samples is also an efficient way to screen for the nucleic acids of viruses, bacteria, or parasites (4,5,(7)(8)(9)(10)(11)(12)(13)(14)(15). However, pooling can decrease the sensitivity of assays due to the dilution of the samples, which is problematic in clinical diagnostics (16).…”
mentioning
confidence: 99%